An emerging role for prdm family genes in dorsoventral patterning of the vertebrate nervous system. Issue 1 (December 2015) - Zannino, Denise; Sagerström, Charles
Abstract The embryonic vertebrate neural tube is divided along its dorsoventral (DV) axis into eleven molecularly discrete progenitor domains. Each of these domains gives rise to distinct neuronal cell types; the ventral-most six domains contribute to motor circuits, while the five dorsal domains contribute to sensory circuits. Following the initial neurogenesis step, these domains also generate glial cell types—either astrocytes or oligodendrocytes. This DV pattern is initiated by two morphogens—Sonic Hedgehog released from notochord and floor plate and Bone Morphogenetic Protein produced in the roof plate—that act in concentration gradients to induce expression of genes along the DV axis. Subsequently, these DV-restricted genes cooperate to define progenitor domains and to control neuronal cell fate specification and differentiation in each domain. Many genes involved in this process have been identified, but significant gaps remain in our understanding of the underlying genetic program. Here we review recent work identifying members of thePrdm gene family as novel regulators of DV patterning in the neural tube. Many Prdm proteins regulate transcription by controlling histone modifications (either via intrinsic histone methyltransferase activity, or by recruiting histone modifying enzymes).Prdm genes are expressed in spatially restricted domains along the DV axis of the neural tube and play important roles in the specification of progenitor domains, as well as in the subsequent differentiation of motor neurons and various types of interneurons. Strikingly, Prdm proteins appear to function by binding to, and modulating the activity of, other transcription factors (particularly bHLH proteins). The identity of key transcription factors in DV patterning of the neural tube has been elucidated previously (e.g. thenkx, bHLH andpax families), but it now appears that an additional family is also required and that it acts in a potentially novel manner.